Impact of extended preplasma on energy coupling in kilojoule energy relativistic laser interaction with cone wire targets relevant to fast ignition - T Yabuuchi; R Mishra; C McGuffey; B Qiao; M S Wei; H Sawada; Y Sentoku; T Ma; D P Higginson; K U Akli; D Batani; H Chen; et al. (New Journal of Physics, 2013)
Cone-guided fast ignition laser fusion depends critically on details of the interaction of an intense laser pulse with the inside tip of a cone. Generation of relativistic electrons in the laser plasma interaction (LPI) with a gold cone and their subsequent transport into a copper wire have been studied using a kJ-class intense laser pulse, OMEGA EP (850 J, 10 ps). We observed that the laser-pulse-energy-normalized copper K α signal from the Cu wire attached to the Au cone is significantly reduced (by a factor of 5) as compared to that from identical targets using the Titan laser (150 J, 0.7 ps) with 60 ×  less energy in the prepulse. We conclude that the decreased coupling is due to increased prepulse energy rather than 10 ps pulse duration, for which this effect has not been previously explored. The collisional particle-in-cell code PICLS demonstrates that the preformed plasma has a significant impact on generation of electrons and their transport. In particular, a longer scale length preplasma significantly reduces the energy coupling from the intense laser to the wire due to the larger offset distance between the relativistic critical density surface and the cone tip as well as a wider divergence of source electrons. We also observed that laser-driven plasma ionization increase in the LPI region can potentially alter the electron density profile during the laser interaction, forcing the electron source to be moved farther away from the cone tip which contributes to the reduction of energy coupling.